Seroprevalence of hepatitis B surface antigen and hepatitis B e antigen among childbearing-age women in Mianyang, China - Min Wang; Hong Li; Yulin Ji; Yuanji Ma; Liping Wang; Tao Ren; Fengsu Hou; Ping Yuan (Journal of Infection in Developing Countries)
Introduction: Few studies have focused on hepatitis B virus (HBV) infection among childbearing-age women. This study explored hepatitis B surface antigen (HBsAg) seroprevalence and hepatitis B e antigen (HBeAg) seroprevalence and their associated factors among childbearing-age women. Methodology: A cross-sectional, population-based study was conducted between June 2013 and October 2013 in Mianyang; women 15–49 years of age were enrolled using a multistage cluster sampling design. Participants completed questionnaires about demographic characteristics and potential factors associated with HBV infection, and provided blood samples for screening HBsAg and HBeAg. The analysis methods included descriptive statistics, Chi-square test, and multivariate logistic regression. Results: Among 62,007 childbearing-age women, 5.66% were HBsAg positive. The HBsAg seroprevalence rates were 7.28% in women 40–44 years of age, 7.0% in Fucheng women, 5.70% in Han women, 6.59% in married women, and 6.60% in agriculture workers. Multivariate models identified having HBsAg-positive family members, and having no self-reported immunization history to be positively associated with HBsAg positivity; being a healthcare worker was negatively associated with HBsAg positivity. Among 3,499 HBsAg-positive childbearing-age women, 9.97% were HBeAg positive. The HBeAg seroprevalence rates were 46.54% in women 15–19 years of age, 10.82% in Fucheng women, 38.51% in single women, and 42.86% in students. Multivariate models identified living in Fucheng and younger age to be positively associated with HBeAg positivity. Conclusions: These findings could provide scientific evidence for the Chinese government to plan efficient health care services and prevention initiatives, and to allocate health resources reasonably for this population.